Design and Control of a Single Phase DC/Rectified AC/AC Inverter for Low THD Applications - Tekgun, Burak; Tekgun, Didem; Alan, İrfan; Badawy, Mohamed O. (Institute of Electrical and Electronics Engineers Inc., 2018)
In this paper, a single phase DC/Rectified AC/AC (DC/RAC/AC) inverter is analyzed and compared to classical single phase PWM inverters. A traditional AC power supply (PS) system consists of a DC/DC converter, a cascaded H-bridge inverter, and a passive filter to generate the sinusoidal output voltage. The presented DC/RAC/AC inverter has a similar structure; however, the control of the cascaded units differ. The presented method generates rectified sine wave at the output of the DC/DC converter unit and the H-bridge inverter alternates the rectified sine wave to generate the full sine wave without having an additional output filter; hence, the switching losses at the H-bridge inverter is limited to the line frequency (50-60 Hz). Moreover, the bulk DC bus capacity at the output of the DC/DC converter is reduced significantly. Therefore, the power consumed by the passive elements are minimized. The circuit modes of operation are analyzed and the system is simulated in Matlab/Simulink environment for both traditional and proposed topologies. Results show that the proposed system is superior to the traditional one in terms of efficiency, generated THD with a simplified control structure, and it offers a reduced system size and cost. © 2019 Elsevier B.V., All rights reserved.
Isahaya Electronics Corporation (IDC); TMEIC
Tekgun, Burak/0000-0003-2720-8816;
Keywords: Fast Control; High Efficiency; Inverter; Low Cost; Low Thd; Reduced Size; Sine Wave Generation; Wide Band Gap; Ac-Ac Power Converters; Bridge Circuits; Cost Reduction; Electric Inverters; Energy Gap; Passive Filters; Fast Control; High-Efficiency; Inverter; Low Costs; Low Thd; Reduced Size; Sine-Wave; Wide Band Gap; DC-DC Converters